The Impact of Mergers and Acquisitions on Company Performance in Emerging Capital Markets - ГригорьеваСветлана Александровна; ТроицкийП. В. (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2012)
Authors: Svetlana A. Grigorieva National Research University The Higher School of Economics grigorievasa@mail.ru P V Troitsky National Research University The Higher School of Economics This paper examines the impact of mergers and acquisitions on corporate performance on the sample of companies from BRIC countries over 2005-2009. Based on the accounting study method we find that the operating performance of firms (measured by EBITDA/Sales ratio) improves subsequent to mergers and acquisitions. We also find that the main determinants of M&A performance for the companies from BRIC countries are the acquirer’s size and friendly character of the deal.